Paraganglioma of the thyroid gland: A case report - Filipović, Aleksandar; Vučković, Ljiljana; Pejakov, Ljubica (Vojnosanitetski pregled, 2014)
Introduction. Thyroid paraganglioma is a very rare malignant neuroendocrine tumor. Immunohistochemical features of thyroid paraganglioma are helpful for the diagnosis. Case report. A 69-year-old female came to hospital with the presence of a growing thyroid nodule of the left lobe. Ultrasonic neck examination showed 5 cm hypoechoic nodule in the left thyroid lobe. Thyroid scintigraphy showed a big cold nodule in the left lobe. Computed tomography (CT) scan showed left lobe thyroid tumor with tracheal deviation on the right site. Extended total thyroidectomy was done. Intraoperative consultation with the pathologist confirmed thyroid cancer. The pathologist diagnosed thyroid paraganglioma on the base of immuohistochemical investigation. This thyroid paraganglioma was positive for neuron-specific enolase, chomogranin A, synaptophysin, and S-100 protein highlighted the sustentacular cells. Tumor cells were negative for thyroglobulin, epithelial membrane antigen, cytokeratin, calcitonin, and carcinoembryonic. After the surgery the patient was treated with chemotherapy, peptide receptor radionuclide therapy, and permanent TSH suppressive therapy. The patient was followed with measurements of thyroid hormone and serum neuron–specific enolase, chromogranin A level, every 6 months. Gastroscopy, colonoscopy, chest and abdomen CT scan as well as further tests (chest x-ray, ultrasound of the neck, and whole body octreotide scintigraphy) were done. No primary neuroendocrine tumor in digestive sistem or in the chest was found. After more than 3 years the patient has no evidence of the recurrent disease. Conclusion. Radical resection of thyroid paraganglioma, followed by chemotherapy and peptide receptor radionuclide therapy, should be considered the treatment of choice in patients with thyroid gland paraganglioma.
Keywords: neuroendocrine tumors; thyroid gland; paraganglioma; diagnosis; surgical procedures; operative; drug therapy